Chronic Obstructive Pulmonary Disease (COPD) in Population Studies in Russia and Norway: Comparison of Prevalence, Awareness and Management - Cook,Sarah; Eggen,Anne Elise; Hopstock,Laila A; Malyutina,Sofia; Shapkina,Marina; Kudryavtsev,Alexander V; Melbye,Hasse; Quint,Jennifer K (International Journal of Chronic Obstructive Pulmonary Disease, 2021)
Sarah Cook,1– 3 Anne Elise Eggen,1 Laila A Hopstock,1 Sofia Malyutina,4,5 Marina Shapkina,4 Alexander V Kudryavtsev,1,6 Hasse Melbye,1,* Jennifer K Quint3,* 1Department of Community Medicine, UiT The Arctic University of Norway, Tromsø, Norway; 2Faculty of Epidemiology and Population Health, London School of Hygiene & Tropical Medicine, London, UK; 3National Heart and Lung Institute, Imperial College London, London, UK; 4Research Institute of Internal and Preventive Medicine, Branch of Institute of Cytology and Genetics, Siberian Branch of the Russian Academy of Sciences, Novosibirsk, Russian Federation; 5Novosibirsk State Medical University, Russian Ministry of Health, Novosibirsk, Russian Federation; 6Northern State Medical University, Arkhangelsk, Russian Federation*These authors contributed equally to this workCorrespondence: Sarah Cook Email sarah.cook@lshtm.ac.ukBackground: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. Despite a high prevalence of smoking and respiratory symptoms, two recent population-based studies in Russia found a relatively low prevalence of obstructive lung function. Here, we investigated the prevalence of both obstructive lung disease and respiratory symptoms in a population-based study conducted in two Russian cities and compared the findings with a similar study from Norway conducted in the same time period.Methods: The study population was a sub-sample of participants aged 40– 69 years participating in the Know Your Heart (KYH) study in Russia in 2015– 18 (n=1883) and in the 7th survey of the Tromsø Study (n=5271) carried out in Norway in 2015– 16 (Tromsø 7) who participated in spirometry examinations. The main outcome was obstructive lung function (FEV1/FVC ratio< lower limit of normal on pre-bronchodilator spirometry examination) with and without respiratory symptoms (chronic cough and breathlessness). In those with obstructive lung function, awareness (known diagnosis) and management (use of medications, smoking ...